Legalitas Pengganti Tanda Tangan Dan Sidik Jari Dalam Pembuatan Akta Notaris Bagi Penghadap Penyandang Disabilitas Fisik - Prim, Febiola Felda; Warman, Kurnia; Syofyan, Syofirman (Nagari Law Review, 2025)
This study discusses the issue related to the notary's obligation to affix the signature and fingerprint of the appearer on the deed minutes as regulated in Article 16 paragraph (1) letter c of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 on Notary Positions. The problem arises when the appearer is a person with physical disabilities who is unable to affix their signature or fingerprint. The purpose of this study is to analyze the regulation regarding the use of signatures and fingerprints on notarial deeds, the legal consequences if the deed minutes are not signed or do not contain the appearer's fingerprint, and alternative substitutes for signatures and fingerprints for persons with disabilities. This research uses a normative juridical method with a descriptive analytical approach and secondary data obtained through library research. The results show that the use of signatures and fingerprints on notarial deeds serves as a form of legal protection and prudence, functioning as additional evidence for the notary and the parties involved. Legally, the absence of a signature or fingerprint on the deed minutes does not invalidate the authenticity and legality of the deed, as long as the appearer's statement is acknowledged by the notary. For persons with physical disabilities, substitutes for signatures and fingerprints can include surrogates, footprints, or lip prints, which are legally accepted as means of individual identification. Thus, the notary can still fulfill administrative obligations without diminishing the authentic value of the deed.